2018
DOI: 10.4103/sjg.sjg_509_17
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient characteristics and magnetically controlled capsule endoscopy findings

Abstract: Background/Aim:Magnetically-controlled capsule endoscopy (MCE) is a potential option for the evaluation of gastric diseases in cases that are unsuited for conventional endoscopy, avoiding discomfort, sedation, and related complications. This retrospective study investigated associations between MCE findings and patient gender, age, and inpatient/outpatient status.Patients and Methods:The data of 580 consecutive patients who underwent MCE from 2015 to 2016 were analyzed. Data included age, gender, indication fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The rate of complete small bowel examination using MCCG varies from 75.1% to 100%. 31,57,58 A prospective cohort study included 49 patients with recurrent or refractory iron deficiency anemia who underwent MCCG and EGD, showing that MCCG had a higher lesion detection rate and higher diagnostic yield in the upper GI tract than conventional EGD, with a better tolerance. 31 In a retrospective study involving 226 patients with suspected small bowel disease (with negative gastroscopy results and GI symptoms), the completion rate of MCCG (NaviCam) for small bowel examination was 97.79%, and the detection rate of small bowel disease was 77.43%, including enterocolitis, ulcers, vascular diseases, polyps, tumors, and diverticula.…”
Section: Level Of Evidence: Moderatementioning
confidence: 99%
See 4 more Smart Citations
“…The rate of complete small bowel examination using MCCG varies from 75.1% to 100%. 31,57,58 A prospective cohort study included 49 patients with recurrent or refractory iron deficiency anemia who underwent MCCG and EGD, showing that MCCG had a higher lesion detection rate and higher diagnostic yield in the upper GI tract than conventional EGD, with a better tolerance. 31 In a retrospective study involving 226 patients with suspected small bowel disease (with negative gastroscopy results and GI symptoms), the completion rate of MCCG (NaviCam) for small bowel examination was 97.79%, and the detection rate of small bowel disease was 77.43%, including enterocolitis, ulcers, vascular diseases, polyps, tumors, and diverticula.…”
Section: Level Of Evidence: Moderatementioning
confidence: 99%
“…The magnetic ball is held at the patient's right shoulder to observe the fundus, the junction of Thus, a shorter GTT may improve the completion rate of a small bowel examination. 38,57 Two studies on robotic-arm MCCG (NaviCam) found that magnetic steering significantly accelerated the passage of the capsule through the pylorus (with a success rate of 59% within 30 min and a reduction of the GTT from 84 to 22 min), and real-time observation of the duodenum under magnetic control improved the detection rate of the duodenal papilla (from 9% to 30%)…”
Section: Level Of Evidence: Lowmentioning
confidence: 99%
See 3 more Smart Citations